Pathogenesis of pathogenic Naegleria amoeba - Chang, S L (Folia parasitologica, 1979)
In brain sections of the Naegleria-caused cases of primary amoebic meningoencephalitis, extensive demyelinization was found in the white matter, besides the severe histopathological changes and large clusters of trophozoites in the grey matter. The myelinoclasis appeared to be a result of a specific phospholipolytic effect, unlike that in post-viral encephalomyelitis, which has been attributed to vascular blockade or hemorrhages. In monkey kidney cell cultures a very early cytopathic effect was observed and traced to the cytolytic property of the seeding culture fluid. Rat brain slices inoculated with Naegleria culture exhibited amoebic growth and demyelinization in 28-52 hours incubation at 35 degrees C. In a chemically defined medium containing sphingomyelin, casein and glucose, the Naegleria produced a limited growth parallelling the clearance of the lipid turbidity during a 72 hour incubation at 35 degrees C. Chromatographic analysis of the turbidity-cleared cultures revealed decomposition of sphingomyeline with liberation of choline, sphingosine and fatty acids. It is, hence, concluded that the pathogenicity of cytopathic effect of pathogenic Naegleria can be attributed to the latter's capacity to liberate a phospholipolytic enzyme or factor during active growth, which "makes holes" in the lipid-rich cytoplasmic membrane of cells as well as demyelinizes nerve tissue.
Keywords: amébiáza; Amoeba; zvířata; sfingomyeliny; Species Specificity; Kidney; ledviny; Sphingomyelins; kultivační techniky; Animals; mozek; krysa rodu Rattus; Rats; Meningoencephalitis; druhová specificita; Amebiasis; Brain; Haplorhini; lidé; Humans; Culture Techniques; meningoencefalitida; Haplorrhini